Sosialisasi Mahasiswa Baru Universitas PGRI Palembang di Kabupaten Ogan Komering Ilir Palembang - Edduar Hendri; Ninin Non Ayu Salmah; Oktariansyah Oktariansyah; Yudi Irwansi; Joni Iswan; Rahmawati Rahmawati; Aprizal Rosadian; M.Nur Arriyanto; Agus Mulyani (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Socialization is a general concept which is defined as a process in which we learn to interact with other people, how to act, think and feel, all of which are important in producing effective social participation. This socialization was carried out as a form of the university's efforts to provide information regarding the acceptance of new students. The method used in this community service activity is providing socialization and promotion of all admission routes and study programs at PGRI Palembang University. In this socialization program, information is also provided regarding the new rules for accepting new students through the report card and written selectionroute. in 2024. With this activity, it is hoped that it will be useful for high school students in South Sumatra to be able to choose a major that suits their talents and interests. Apart from socialization activities, introducing the PGRI Palembang University Campus to high school and vocational school students in Ogan Regency Komering Ilir Palembang in this activity also socialized all majors, both undergraduate and postgraduate, for teachers who taught at the high school. As one university, PGRI Palembang University also holds socialization for new student admissions every year.